Jurnal REPRESENTASI NILAI-NILAI PENDIDIKAN AGAMA HINDU DALAM UPACARA BALIGIA DI DESA JUNGUTAN, KECAMATAN BEBANDEM, KABUPATEN KARANGASEM: REPRESENTASI NILAI-NILAI PENDIDIKAN AGAMA HINDU DALAM UPACARA BALIGIA DI DESA JUNGUTAN, KECAMATAN BEBANDEM, KABUPATEN KARANGASEM - Mantra, Ida Bagus Genter Sidhi Mantra; Perbowosari, Heny; Muliani, Ni Made (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2025)
The Baligia ceremony in Jungutan Village, Bebandem District, Karangasem Regency has a uniqueness that distinguishes it from Baligia ceremonies in other regions, especially in Bali, namely that the Baligia ceremony is carried out specifically and takes the most important levels, as a form of final respect from the sentana (descendants) to all Puspa and Name (spirits) who are purified. And this Baligia ceremony is carried out for almost a year. Based on this background, the problems obtained are; (1) How is the Representation of Hindu Teachings in the Baligia Ceremony in Jungutan Village, Bebandem District, Karangasem Regency? (2) What are the characteristics of the Baligia Ceremony in Jungutan Village, Bebandem District, Karangasem Regency? (3) What are the Values of Hindu Education in Baligia Ceremony in Jungutan Village, Bebandem District, Karangasem Regency? This study aims to gain a fundamental understanding related to the Representation of Hindu Education Values, namely (1) To describe the Representation of Hindu Teachings in the Baligia Ceremony in Jungutan Village, Bebandem District, Karangasem Regency, (2) To describe the Characteristics of the Baligia Ceremony in Jungutan Village, Bebandem District, Karangasem Regency, (3) To describe the Values of Hindu Education in the Baligia Ceremony in Jungutan Village, Bebandem District, Karangasem Regency. From this research, it is expected to be a reference and provide benefits for all parties. This research uses a type of qualitative research with the theories used to analyze the problem are Representation Theory, Ritual Theory, and Value Theory to dissect the research problem. Data collection techniques are interviews, documentation, and literature studies. The data that has been collected is then analyzed by descriptive analysis methods with steps of data collection, data reduction, data presentation, and data verification. The results of this study show (1) the representation of Hindu teachings in the Baligia Ceremony is divided into three, namely; sincere and sincere holy sacrifice, Atman's death to Brahman, and the spirit of togetherness and mutual assistance. (2) The characteristics of the Baligia Ceremony, namely Peminehan Anyar which is a ceremonial procession to obtain chess oil through a special process, which is obtained by filtering from feces, urine and milk from purified oxen. (3) The value of Hindu education contained in the Baligia ceremony is the value of tattwa education, the value of moral education, and the value of event / ceremony education.